Population Structure of Steelhead in Coastal California. Issue 1 (6th January 2014) - Garza, John Carlos; Gilbert‐Horvath, Elizabeth A.; Spence, Brian C.; Williams, Thomas H.; Fish, Heidi; Gough, Stephen A.; Anderson, Joseph H.; Hamm, David; Anderson, Eric C.
Abstract: Steelhead Oncorhynchus mykiss are the most widespread of the Pacific salmonids Oncorhynchus spp. and are found in nearly all basins within their native range around the northern Pacific Rim. Here, we elucidate genetic population structure of steelhead in coastal basins from most of their coastal‐California range using variation at 15 microsatellite loci. Juvenile fish from 60 streams in 40 river basins were sampled in a single year from a single cohort. As samples of juvenile salmonids often contain sibling groups, a method was implemented to identify and eliminate all but one member of larger sibships. This, in conjunction with a rigorous sampling protocol and hierarchical sampling design, provided substantially improved resolution for understanding patterns of migration and demography. A pattern of isolation by distance was evident, as indicated by both phylograms that were largely concordant with geography and a significant regression of genetic distance on geographic distance, indicating that population structure is largely determined by migration that is dependent upon geographic distance. Within‐basin genetic distances tended to be smaller than those between basins, although there was substantial overlap between them. Using a Bayesian clustering method to evaluate signals of population structure above the level of a river basin, four geographic sites were identified where genetic composition shifted abruptly. These areas largely correspond to major geographic features of the coastline: San Francisco and Humboldt bays and two extended sections of coast (the so‐called Lost Coast and Russian Gulch areas) with no streams reaching inland more than several kilometers. Only one of these boundaries is concordant with the current delineation of steelhead Distinct Population Segments designated under the U.S. Endangered Species Act. Finally, there was a strong correlation between latitude and genetic variation, with fewer alleles present in the south, a pattern consistent with generally smaller population sizes in the south.